Alfalfa Cost-Return Budget in South Central and Southeast Kansas - Dumler, Troy J.; Shoup, Douglas (My University, 2008)
This publication contains information for a projected budget reflecting expected income and cost based on alfalfa production in south central and southeast Kansas.
MF363_2008_10
Keywords: MF363; Economics; Crops; MF